Evidence of altered pressure pain thresholds in persons with disorders of consciousness as measured by the Nociception Coma Scale–Italian version. Issue 8 (17th November 2018) - Sattin, Davide; Schnakers, Caroline; Pagani, Marco; Arenare, Francesca; Devalle, Guya; Giunco, Fabrizio; Guizzetti, GianBattista; Lanfranchi, Maurizio; Giovannetti, Ambra M.; Covelli, Venusia; Bersano, Anna; Nigri, Anna; et al.
ABSTRACT: Pain assessment in patients with disorders of consciousness (DoC) is a controversial issue for clinicians, who require tools and standardised procedures for testing nociception in non-communicative patients. The aims of the present study were, first, to analyse the psychometric properties of the Italian version of the Nociception Coma Scale and, second, to evaluate pressure pain thresholds in a group of patients with DoC. The authors conducted a multi-centre study on 40 healthy participants and 60 DoC patients enrolled from six hospitals in Italy. For each group an electronic algometer was used to apply all nociceptive pressure stimuli. Our results show that the Italian version of the NCS retains the good psychometric properties of the original version and is therefore suitable for standardised pain assessment in clinical practice. In our study, pressure pain thresholds measured in a group of patients in vegetative and minimally conscious state were relatively lower than pain threshold values found in a group of healthy participants. Such findings motivate additional investigation on possible pain sensitisation in patients with severe brain injury and multiple co-morbidities, and on application of tailored therapeutic approaches useful for pain management in patients unable verbally to communicate their feelings.